Mechanics of impression evidence - Pierce, David (Auerbach Publications, 2011)
As forensic technology becomes more sophisticated, courts are demanding more scientific content and juries are expecting meticulous confirmation of facts alleged. Greater attention is now paid to increasingly finer details and improved methods of describing every form of evidence. Applying physics, chemistry, and engineering to the process of analysis and interpretation, Mechanics of Impression Evidence reflects the shift to these heightened standards and offers a starting point for significant change in the way that impression evidence is considered, utilized, and presente.
Includes bibliographical references and index. - Print version record
Keywords: Criminal investigation; Evidence, Criminal; Forensic sciences; Forensic Sciences; Enquêtes criminelles; Preuve (Droit pénal); Criminalistique; forensic science; LAW; Forensic Science